2021
DOI: 10.3390/ani11082263
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of lncRNA and mRNA in Testes of Landrace and Hezuo Boars

Abstract: Chinese HZ boars are typical plateau miniature boars characterized by precocious puberty, which is closely related to testicular development and spermatogenesis. Accumulating evidence indicates that lncRNA is involved in the testicular development and regulation of spermatogenesis. However, little is known about the lncRNA precocious regulation in testicular development and spermatogenesis on early sexual maturity of HZ boars. Thus, we investigated the expression and characterization of lncRNA and mRNA in 30-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…LncRNAs in Min pigs share similarities in structure and classification with their counterparts in mammals ( 27 29 ). The number of lncRNAs identified here is somewhat higher than that in other pig breeds such as Duroc, Landrace, and Guizhou miniature pigs ( 30 33 ), which might be caused by the rich genetic resource in Min pigs, and also by the different screening criteria used for lncRNA characterization.…”
Section: Discussionmentioning
confidence: 56%
“…LncRNAs in Min pigs share similarities in structure and classification with their counterparts in mammals ( 27 29 ). The number of lncRNAs identified here is somewhat higher than that in other pig breeds such as Duroc, Landrace, and Guizhou miniature pigs ( 30 33 ), which might be caused by the rich genetic resource in Min pigs, and also by the different screening criteria used for lncRNA characterization.…”
Section: Discussionmentioning
confidence: 56%
“…The mRNA expression data of 12 samples from our previous study were used for a pairwise integrated analysis ( 31 ). To explore miRNAs related to precocious puberty in HZ boars, we screened 158 DE miRNAs from the Ha and Hb, Hb and Lb groups.…”
Section: Resultsmentioning
confidence: 99%
“…It can improve the utilization of female animals, shorten the generation interval of excellent females, and accelerate the genetic breeding process. Our previous works have shown that HZ boars have reached sexual maturity at 4 months of age ( 31 ). To explore potential regulatory mechanisms of early sexual maturation in HZ boars, the serum hormones (T, E 2 , FSH, and LH) of HZ and LC boars at 30, 90, 120, 180, and 240 days were measured and compared, and the miRNAs in the testes of HZ and LC boars at 30 and 120 days were identified and comparatively analyzed using small RNA-Seq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs can regulate the expression of functional genes in a variety of ways. lncRNAs regulate the expression of neighboring functional genes through cis -mRNA and can also regulate distant target genes through trans -mRNA ( 18 ). In addition, lncRNAs could serve as miRNA sponges and thereby impair miRNA-mediated gene silencing ( 19 ).…”
Section: Introductionmentioning
confidence: 99%